IMPLEMENTASI SISTEM MONITORING HOTSPOT JARINGAN KOMPUTER MENGGUNAKAN MIKHMON DENGAN METODE WIRELESS DISTRIBUTION SYSTEM (STUDI KASUS: WARKOP IDOL’S SAWANGAN DEPOK) - Muhammad Rafif Misbahuddin; Dede Sahrul Bahri (CV. Multi Kreasi Media, 2023)
The number of internet users in the world is increasing rapidly, its use is usually applied to smartphones, laptops, computers and other information technologies that are used to work, find information, get entertainment, and so on. The problems that occur at Warkop Idol are as follows, when the internet bandwidth speed drops due to the large use of internet bandwidth by visitors, one of the causes is the occurrence of excessive bandwidth hogs on the one hand. With the increase in internet bandwidth speed, it affects the convenience of visitors who use free wi-fi access. In addition, some visitors only use wifi, only order 1 type of food or drink with a duration that exceeds the normal limit. Meanwhile, other visitors who just visited did not get a seat because the time was limited. To overcome this problem, a computer network design was made using the wireless distribution system (wds) method and a web-based network monitoring system that would later be able to maximize the internet network in the idol warkop. In this study using the PPDIOO implementation method (Prepare, Plan, Design, Implement, Operate, and Optimize) where the flow and stages used include analysis, network topology design, implementation, and testing. The result of this research is in the form of a computer network monitoring system which is expected to facilitate the internet network processing process at Warkop Idols.